1994
DOI: 10.1038/372336a0
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure at 2.2 Å resolution of the MHC-related neonatal Fc receptor

Abstract: The three-dimensional structure of the rat neonatal Fc receptor (FcRn) is similar to the structure of molecules of the major histocompatibility complex (MHC). The counterpart of the MHC peptide-binding site is closed in FcRn, making the FcRn groove incapable of binding peptides. A dimer of FcRn heterodimers seen in the crystals may represent a receptor dimer that forms when the Fc portion of a single immunoglobulin binds. An alternative use of the MHC fold for immune recognition is indicated by the FcRn and Fc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
208
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 309 publications
(224 citation statements)
references
References 45 publications
8
208
0
3
Order By: Relevance
“…The enlarged gold particles were in locations suggesting they represented enhanced 1.4 nm Nanogold attached to Fc that was bound to FcRn: near the inner membrane leaflets of tubular vesicles (Figure 4a and 5) and multivesicular bodies (Figure 4b), and in the extracellular space near the basolateral surface (Figure 4c, 5d). Notably, the majority of enhanced Au-Fc particles in duodenal samples were found within a 6-7 nm distance from a membrane, implying attachment to FcRn, which has an ∼5 nm ectodomain (Burmeister et al, 1994). In the ileum, we again saw enhanced gold particles inside degradative vesicles (Figure 4d), consistent with fluid phase uptake in this region of the neonatal intestine.…”
Section: A New Methods To Enlarge 14 Nm Gold Clusters In Hpf/fsf Samplessupporting
confidence: 65%
“…The enlarged gold particles were in locations suggesting they represented enhanced 1.4 nm Nanogold attached to Fc that was bound to FcRn: near the inner membrane leaflets of tubular vesicles (Figure 4a and 5) and multivesicular bodies (Figure 4b), and in the extracellular space near the basolateral surface (Figure 4c, 5d). Notably, the majority of enhanced Au-Fc particles in duodenal samples were found within a 6-7 nm distance from a membrane, implying attachment to FcRn, which has an ∼5 nm ectodomain (Burmeister et al, 1994). In the ileum, we again saw enhanced gold particles inside degradative vesicles (Figure 4d), consistent with fluid phase uptake in this region of the neonatal intestine.…”
Section: A New Methods To Enlarge 14 Nm Gold Clusters In Hpf/fsf Samplessupporting
confidence: 65%
“…The stoichiometry of the interaction between FcRn and its ligand has been a matter of debate (20, 26 -29). In the cocrystals, a long, repeating oligomeric ribbon with a 2n:n stoichiometry was observed, in which FcRn dimers are bridged by Fc molecules so that every Fc dimer interacts with two receptors (38). Studies also suggested that the 2:1 FcRn-Fc complex is formed in solution, although FcRn is not capable of dimerization in these conditions (28,29).…”
Section: Discussionmentioning
confidence: 93%
“…In one binding mechanism, the two FcRn molecules bind symmetrically to two Fc monomers in a dimeric Fc, and in the other, the two FcRn bind asymmetrically: the first FcRn molecule binds to an Fc monomer in a similar manner to the FcRn-mFc binding, and the binding of the second FcRn to Fc must have a low affinity, to give an overall comparable K D to the one-step FcRn-mFc binding. The latter mechanism seems more likely because a bent, asymmetrical Fc structure was found in the 1:1 FcRn/hdFc (heterodimeric Fc that can only bind one FcRn) cocrystal (38). The low affinity of the second FcRn binding is probably due to the conformational change in Fc caused by the binding of the first FcRn.…”
Section: Discussionmentioning
confidence: 99%
“…As with all members of the family, a prominent feature of the ␣ 1 and ␣ 2 domains is a pair of opposing ␣-helices that enclose the binding groove for peptides or (glyco)lipids in MHC proteins. In FcRn, HFE, and MIC-A, the groove is closed, and there is no evidence for ligand binding within the region between the helices, although each interacts with other proteins (15)(16)(17). In ZAG, however, the x-ray crystal structure shows that the groove is open and contains an additional electron density ascribed to an unidentified ligand ( Fig.…”
mentioning
confidence: 99%